Genetic Changes in Ovarian Cancer - Kar-San Ling; Gin-Den Chen; Horng-Jyh Tsai; Maw-Sheng Lee; Po-Hui Wang (Elsevier, 2005)
Ovarian cancer is among the most lethal of all malignancies in women. While chemotherapy is the preferred treatment modality, chemoresistance severely limits treatment success. Chemoresistance may be multifactorial and related to multiple mechanisms, such as alterations in drug transport, changes in cellular proteins involved in detoxification, altered drug target, changes in DNA repair mechanisms, increases in drug damage tolerance, and genetic changes. Genetic changes appear to be associated directly with the loss of chemosensitivity in ovarian cancer. In this review, we detail the possible genetic changes that occur in ovarian cancer, including activation of specific oncogenes, inactivation of tumor suppressor genes, and downregulation of metastasis suppressor genes.